Sustained Plasma Fibrinogen Elevation in Subtotal Nephrectomized Rats: Effect of Cilazapril, an Angiotensin-Converting Enzyme Inhibitor - Koh-ichi Sugimoto; Shuichi Tsuruoka; Akio Fujimura (Elsevier, 2004)
The present study was undertaken to examine whether plasma fibrinogen persistently elevates in subtotal nephrectomized rats, an animal model with inflammatory renal changes. Eight weeks after the induction of 5/6 nephrectomy in male Wistar rats, plasma fibrinogen concentration was determined for the next 12 weeks in the animals received vehicle or an angiotensin-converting enzyme inhibitor, cilazapril (1 or 10 mg/kg per day) orally. In the vehicle-treated nephrectomized rats, plasma fibrinogen concentration significantly (P<0.001) increased (from 127.3 ± 4.6 [S.E.M.] to 182.3 ± 5.2 mg/dL) compared with that in the control rats (from 118.0 ± 2.0 to 153.5 ± 5.4 mg/dL). Cilazapril attenuated the increases in plasma fibrinogen concentration in a dose-dependent manner. Serum concentration of monocyte chemoattractant protein-1, a key macrophage chemoattractant and activator, increased in the vehicle-treated nephrectomized rats, which was also reduced by cilazapril. These results suggest that plasma fibrinogen elevates persistently in the nephrectomized rats. Local inflammation may be involved in the hepatic fibrinogen synthesis in this model. Keywords:: nephrectomized rat, cilazapril, fibrinogen, monocyte chemoattractant protein-1, inflammation